Evaluating Workload: A Collaborative Approach between Dean and Department Chair - Melissa J Marcucci Ph.D.; Sandra G Affenito Ph.D., R.D. FAND (Academic Chairpersons Conference Proceedings, 2017)
Faculty workload calculations are complex and an institution’s mission directs the level of faculty participation in each teaching, scholarship and service. The University of Saint Joseph (USJ; West Hartford, Connecticut) transitioned from a college to a university, necessitating reexamination of faculty workload policy. The review was conducted collaboratively between senior administration and key faculty to understand best practices in calculating teaching workload. A review of best practice, evaluation of workload policies at a defined set of peer institutions, and an internal investigation of the types of course offered by USJ faculty was examined.
Keywords: faculty workload; liberal arts university; laboratory course instruction